(untitled) (Journal of Computational Mathematics, 1994)
A preconditioning method for the finite element stiffness matrix is given in this paper. The triangulation is refined in a subregion; the preconditioning process is composed of resolution of two regular subproblems; the condition number of the preconditioned matrix is O(1+logHh), where H and h are mesh sizes of the unrefined and local refined triangulation respectively.